ANNUAL CHANGE OF ESTIMATED GLOMERULAR FILTRATION RATE IN HEALTHY INDIVIDUALS - Filipovski, Stefan; Karanfilovski, Vlatko; Karanfilovikj, Angela; Nikolov, Panche; Bedzheti, Blerim; Sterjova, Zaklina; Gjorgjievski, Nikola; Janevski, Zoran; Rambabova Busletikj, Irena; Trajceska, Lada; Spasovski, Goce (Journal of Morphological Sciences; Vol 7 No 1 (2024): JMS, 2024)
Physiologically, GFR level should be stable up to the end of the fifth decade of life. When measured more frequently, wide dispersion of GFR results have been seen, but, after 5 th decade GFR is expected to reduce by 1ml/min/1,73m2 yearly. The aim of this study was to calculate the change of estimated GFR on annual level and its correlations in healthy individuals. This was a retrospective observational study on 62 healthy subjects during 6 years. Demographical characteristics as gender, age, BMI, obesity (defined as BMI above 30kg/m 2 ) and annual creatinine were obtained from medical files at the general practitioner. Serum creatinine level was measured at one biochemical laboratory. eGFR was calculated with CKD EPI formula. Calculation of the mean annual GFR change (δGFR) was done through the method of data smoothing. Statistics: Continuous variables are shown as average and standard deviation and the nominal ones with number and percent.  GFR change was correlated with age and BMI. Comparative analyses of δGFR in relation to gender and obesity was done by non-parametric Mann-Whiney U test. P was considered significant if less than 0.05. Mean age of the study group was 39.5 years, dominantly male (78%). Mean BMI was 26,3 ± 3.81 kg/m 2 , 13% were obese. The mean annual GFR fluctuated (101.8 ± 5.56; 108.0 ± 31.04; 102.8 ± 18.28;103.2 ± 20.49; 99.10 ± 24.28; 103.55 ± 20.74 mL/min/1.73m 2 , respectively).  The δGFR median value was 2.3 mL/min/1.73m 2 with range of -23 to +20, and its correlations with age and BMI were insignificant (r= -0.058, p=0.681, r= 0.128, p=0.111, respectively). The δGFR did not differ significantly between genders and obese vs nonobese subjects (p=0.577; p=0.768, respectively). This study demonstrated that annual GFR change wasn’t correlated to age, gender and BMI. It also elucidated the fact of a high variable eGFR levels and its annual decline in presumed healthy persons. This fact emphasizes the need for thorough evaluation of the candidates for kidney donors, especially when applying the expanded criteria. Key words: GFR, healthy subjects, kidney function decline, donors.